A review on social media phishing: factors and countermeasures - Chung, Jetli; Koay, Jing-Zhi; Leau, Yu-Beng (Springer Verlag, 2021)
With the rapid growth in the number of social media users, the reported cases of phishing attack on social media are also increasing. Phishing is an attack that takes advantage of users’ trust, attempts to deceive the victim into compromising their credentials. This review paper presents the factor that causes social media sites to become the favorite target for cybercriminals to deploy phishing attacks. Apart from that, this paper also studies the countermeasures in protecting social media users from phishing attacks by reviewing existing works to highlight the current issues as well as provide a perspective for future research.